2017
DOI: 10.1371/journal.pone.0179492
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of HDL on NADPH oxidase-derived super oxide anion mediates hypoxia-induced cardiomyocyte apoptosis

Abstract: Cardiovascular diseases are the leading cause of death of death in Taiwan. Atherosclerosis can lead to serious problems, including heart attack, stroke, or even death. Coronary heart disease (CHD) occurs when plaque builds up in the coronary arteries to cause the ischemic heart disease which will enhance myocardial remodeling and also induce myocardial hypoxia. High density lipoprotein (HDL) has been proposed to have cardio-protective effects. Under hypoxic conditions (1%O2 for 24hr), in H9c2 cells, reactive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…During the hypoxic condition, down regulation of the survival protein,p‐AKTser473 and anti‐apoptotic protein BCL2 with upregulation of pro‐apoptotic proteins, Bax and caspase‐3 expressions promote apoptosis of cardiac cells. It has been found that NOX mediated ROS is responsible for apoptosis in cardiomyocytes under hypoxia conditions through AT1 and PKC activation 53 . Obstructive sleep apnea (OSA) mediated chronic intermittent hypoxia (CIH) is also involved in NOX‐2 mediated ROS generation 54 .…”
Section: Human Pathologies and Nox Connectionsmentioning
confidence: 99%
“…During the hypoxic condition, down regulation of the survival protein,p‐AKTser473 and anti‐apoptotic protein BCL2 with upregulation of pro‐apoptotic proteins, Bax and caspase‐3 expressions promote apoptosis of cardiac cells. It has been found that NOX mediated ROS is responsible for apoptosis in cardiomyocytes under hypoxia conditions through AT1 and PKC activation 53 . Obstructive sleep apnea (OSA) mediated chronic intermittent hypoxia (CIH) is also involved in NOX‐2 mediated ROS generation 54 .…”
Section: Human Pathologies and Nox Connectionsmentioning
confidence: 99%
“…Severe hypoxic environmental condition dramatically appeared after ACL injury is generally considered as a major reason leading to the difficulty of ACL repair due to its adverse regulatory effects on matrix metalloproteinase 2 expression levels (Wang et al, ). What’s more, numbers of studies confirmed that severe hypoxia was harmful to the cell survival, such as cardiomyocyte (Wen et al, ), osteoblasts (Ma et al, ), or giloma cell (Brucker, Maurer, Harter, Rieger, & Steinbach, ). Besides, it was indicated that some ligament cells or tenocytes would undergo a hypoxic environmental condition after injury and cell apoptosis was induced (Aukkarasongsup, Haruyama, Matsumoto, Shiga, & Moriyama, ; Millar et al, ; Song, Zhou, Shu, & Ni, ).…”
Section: Introductionmentioning
confidence: 97%
“…heart failure) [46,47]. Cardiorenal "connectors" such as erythrocyte superoxide dismutase (SOD1), GSH, and NADPH have also been used to measure kidney and heart injury [48][49][50][51][52][53].…”
Section: Oxidative Stressmentioning
confidence: 99%